Proceedings : Asian Multicity Epidemiology Work Group. - Navaratnam, Profesor Madya (Dr.) V.; Foong, Dr. , Kin; Tan, Bee Leng (Pusat Penyelidikan Dadah dan Ubat-Ubatan Universiti Sains Malaysia, 1992)
The escalation of the problems associated with substance abuse in the late 70's and 80's has led countries to search for solutions and tools to assist in controlling the situation. The political will to address this question was manifested in the convening of the United Nations International Conference on Drug Abuse and Illicit Trafficking• (ICDAIT) in 1987.